KEBIJAKAN RAJA MENGENAI HARTA WARISAN KELUARGA YANG TERGOLONG KRÄ€NGAN PADA ZAMAN KERAJAAN BALI KUNO YANG HINDUISTIS - Semadi Astra, I Gde (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
This article discusses one of the facets of life in ancient Balinese times, namely inheritance, espe- cially family estate belonging to krÄngan (family without children/ descendants), or more precisely the kingâ€™s policy regarding the inheritance of a childless family. There are three matters concerning the kingâ€™s policy on the subject which the writer would like to answer based on the data already found, namely (a) of the principal ratios of inheritance of the family internally, (b) about the parties who have a share of the property, and (c) of the philosophical view underlying the distribution. First, the principal ratio of the division of inheritance used by the king is 1: 2 in the sense that one-thirds of the husbandâ€™s inheritance is the wifeâ€™s right and two-thirds is the right of the husband. Secondly, the inheritance part of krÄngan ampung belonging to the movable property is placed on the sacred building of Hyang Api and belonging to immovable property that is placed on the holy building of Hyang Tanda. Thirdly, the philosophical foundation underlying the kingâ€™s policy is that the property possessed by humans in general is as a â€œborrowing itemâ€ that should not be taken to another world.